2009
DOI: 10.1002/jssc.200800635
|View full text |Cite
|
Sign up to set email alerts
|

Single‐drop microextraction followed by in‐syringe derivatization and GC‐MS detection for the determination of parabens in water and cosmetic products

Abstract: A single-drop microextraction (SDME) method followed by in-syringe derivatization and GC-MS determination has been developed for analysis of five parabens, including methyl, ethyl, isopropyl, n-propyl and n-butyl paraben in water samples and cosmetic products. N,O-Bis(trimethylsilyl)acetamide (BSA) was used as derivatization reagent. Derivatization reaction was performed inside the syringe barrel using 0.4 microL of BSA. Parameters that affect the derivatization yield such as temperature and time of the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 33 publications
0
48
0
1
Order By: Relevance
“…Moreso the derivatization process takes a shorter time at room temperature. Saraji and Mirmahdieh, (2009) studied the influence of different parameters on the in-syringe derivatization process using BSA were three parameters, the amount of the BSA, the reaction time and the reaction temperature were investigated to achieve the highest derivatization reaction yield. The results showed that 0.2 µL volume of BSA derivatization reagent is enough to obtain the maximum derivatization reaction yield for all compounds in 2 min time at room temperature.…”
Section: Bis(trimethylsilyl)-acetamide (Bsa)mentioning
confidence: 99%
“…Moreso the derivatization process takes a shorter time at room temperature. Saraji and Mirmahdieh, (2009) studied the influence of different parameters on the in-syringe derivatization process using BSA were three parameters, the amount of the BSA, the reaction time and the reaction temperature were investigated to achieve the highest derivatization reaction yield. The results showed that 0.2 µL volume of BSA derivatization reagent is enough to obtain the maximum derivatization reaction yield for all compounds in 2 min time at room temperature.…”
Section: Bis(trimethylsilyl)-acetamide (Bsa)mentioning
confidence: 99%
“…This relationship indicates that SDME quantification is feasible before reaching partition equilibrium once the SDME conditions and the extraction time are held constant. 26,27 An extraction time of 25 min was selected as a compromise between the analyte response and the time of analysis.…”
Section: Optimization Of the Microextraction With In Situ Derivatizationmentioning
confidence: 99%
“…Contradictory opinions on the toxicity and carcinogenicity of parabens [3] According to the literature, methods for preconcentration of parabens, which are based on the singl-drop liquid microextraction combines with silylation [5], the dispersion liquid-liquid microextraction (DLLME) without [6] or with derivatization by acetic anhydride [7], followed by chromatographic determination are known.…”
Section: Introductionmentioning
confidence: 99%